Perilaku Adaptif Mahasiswi yang telah Menikah dalam Penyelesaian Studi - Wardani, Dwi Sri Diah; Musa, Dahniar Th.; Yuliono , Agus (Universitas Cenderawasih, 2024)
This research describes the adaptive behavior of married female students while studying from an anthropological perspective. The main focus of this research is how female students manage their dual roles as wives and students, with special emphasis on adaptive behavior. A qualitative approach was used, involving participant observation and in-depth interviews with female students who faced this situation. The results show that college students who marry while studying develop unique adaptive behavioral strategies to overcome daily challenges. This dual role not only impacts academic aspects, but also the social and emotional dimensions of female students. Cultural factors, social support, and community expectations play a major role in shaping the adaptive behavior of female students. This research makes an important contribution to understanding how female students can successfully manage their dual roles, especially in specific cultural contexts. In conclusion, this research describes in detail the complex dynamics of adaptive behavior of married female students in anthropological studies.Top of Form